Cash in the City : Emerging Lessons from Implementing Cash Transfers in Urban Africa - Gentilini, Ugo; Khosla, Saksham; Almenfi, Mohamed (World Bank, Washington, DC, 2021)
Poverty and crises are rapidly â€œurbanizingâ€ . Yet experience with operationalizing cash transfers in urban areas is limited. This paper captures early lessons from a new generation of urban cash transfer responses to Covid-19 in eleven African countries. The analysis contextualizes such initiatives within a longer-term trajectory of urban social protection programs from the early 2000s. A range of lessons emerge around design and implementation, partnerships, institutions and political economy, strategic issues, and evidence and learning.